Factors Associated With Willingness to Pay for Primary Health Care Services in South Africa: A Cross-Sectional Survey of Medical Schemes Members - Evelyn Thsehla; Charles Hongoro; Jacqui Miot; Kate Kgasi; Edmore Marinda; Esnath Maramba; Alister Chabi; Barry Childs; Olurotimi Modupe; Olufunke Alaba (SAGE Publishing, 2024)
The cost of healthcare is an issue of concern for both consumers and funders of healthcare in South Africa. The country spends approximately 8% of GDP on health care. Health care is financed through the public sector which covers 86% of the population and the private sector which covers 14% of the population. Medical schemes are the main source of healthcare financing in the private sector. Services covered by medical schemes include chronic diseases, emergencies, diagnosis, and treatment of a selected number of diseases. Primary health care services such as screening are limited. The aim of this study was to assess factors associated with members of medical schemes' willingness to pay for a primary health care package in the private sector. A cross-sectional survey was conducted amongst principal members of medical schemes between July and September 2020. All principal members with access to an online questionnaire were eligible to participate in this study. Logistic regression was used to identify factors associated with willingness to pay for primary health care services. A total of 6512 members of medical schemes participated in the study. Thirty-five percent of the participants were willing to pay for the primary health care package. Factors influencing willingness to pay included marital status, employment status, income and household size. The study highlights the need for policymakers to consider socioeconomic factors when designing health care policies.